2012
DOI: 10.1039/c2ja10335d
|View full text |Cite
|
Sign up to set email alerts
|

Brewing and stewing: the effect of culturally mediated behaviour on the oxygen isotope composition of ingested fluids and the implications for human provenance studies

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 35 publications
(56 reference statements)
1
139
0
1
Order By: Relevance
“…Puceat et al (2010) found as much as two per mil variation in phosphate oxygen isotopes measured in bones from fish raised within the same controlled-environment tank, and it is to be reasonably assumed that human environments, being less controlled, would produce a significant level of within-population variation. Similarly, human dietary behavior may also produce variation in oxygen isotopes measured in enamel; although natural evaporative processes do not significantly alter the δ 18 O values of drinking water , consumption of brewed alcoholic drinks, boiled drinks, and stewed foods may enrich the δ 18 O of human enamel by as much as 2.3‰ (Brettell et al, 2012). Although most of these influences must be taken into account, climate change was not found to be a statistically significant factor in altered oxygen isotope values in this study; although the historical timeframe made the end of the MWP and the transition to the Little Ice Age a relevant consideration, a one-way analysis of variance (ANOVA) between the means of age cohorts found no significant differences (P <0.05).…”
Section: Defining the Local Rangementioning
confidence: 99%
“…Puceat et al (2010) found as much as two per mil variation in phosphate oxygen isotopes measured in bones from fish raised within the same controlled-environment tank, and it is to be reasonably assumed that human environments, being less controlled, would produce a significant level of within-population variation. Similarly, human dietary behavior may also produce variation in oxygen isotopes measured in enamel; although natural evaporative processes do not significantly alter the δ 18 O values of drinking water , consumption of brewed alcoholic drinks, boiled drinks, and stewed foods may enrich the δ 18 O of human enamel by as much as 2.3‰ (Brettell et al, 2012). Although most of these influences must be taken into account, climate change was not found to be a statistically significant factor in altered oxygen isotope values in this study; although the historical timeframe made the end of the MWP and the transition to the Little Ice Age a relevant consideration, a one-way analysis of variance (ANOVA) between the means of age cohorts found no significant differences (P <0.05).…”
Section: Defining the Local Rangementioning
confidence: 99%
“…Therefore, δ 18 O recorded in skeletons can be used to identify individuals who had access to a different water supply than rest of the local population. However, the suitability of δ 18 O to this application is still debated because for example, food preparation and drinking fermented beverages can alter isotopic ratio (Brettell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…BL15 and BL44 have δ 18 O values higher than any yet reported from Roman Britain, whilst BL2 and BL45 are higher than, but within measurement error of, the highest previously reported value, which was for a decapitated individual from Driffield Terrace York (6Drif-21), interpreted as a possible gladiator and immigrant (Müldner, et al, 2011b). Evans et al (2012) …”
Section: Mobilitymentioning
confidence: 79%
“…Other processes can also alter human δ 18 O. Humans can also elevate the δ 18 O value of their drinking water by processes such as boiling and brewing (Brettell, et al, 2012), and this must be allowed for in interpretation (for a full discussion of these issues see, Lightfoot…”
Section: Isotope Analysismentioning
confidence: 99%